Memories of glass : a novel - Dobson, Melanie (Tyndale House Publishers, Inc., 2019)
In 1942 Holland, childhood friends Josie and Eliese partner with a few other citizens to rescue Eliese's son and hundreds of other Jewish children awaiting deportation, but dangerous secrets could derail their mission.